Stateless Children’s Access to Tertiary Education - Hasni, Nur Athirah Syuhada; Azman, Nurshahirah; Ismail, Muhammad Nashriq (Selangor Humaniora Review, 2021)
Stateless children have become a major concern in Malaysia for quite some years and the government is continuously making efforts in solving the matter and providing the best they can for these children. In 2018, the then Deputy Prime Minister had instructed government schools to accept stateless children as their students if they can show relevant documents as proof of citizenship application. However, the education journey of these children is incomplete as they can only finish secondary school but has almost no access to tertiary education especially in public institutions. This research aimed to examine the right of education for stateless children with the main objective to identify their access for tertiary education in Malaysia. The method used in the study will be primarily based on the qualitative research methodology which comprises of the doctrinal analysis and empirical study approach. It was found that their fight for tertiary education is rarely being reported and the only mean for them to further their study is to be noticed by the government or private institutions through medias. Sadly, failure in such means that they would either need to pay the tuition fees in private institutions on their own or forget their dreams to pursue higher education.